Predation enforcement options: An evaluation using a Cournot framework - Kai Hüschelrath; Jürgen Weigand (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The paper characterises the building blocks of a framework to enforce antipredation rules and subsequently evaluates selected enforcement options in a Cournot-type duopoly predation model. Differentiating between a no rule approach, an ex ante approach and two ex post approaches, it is shown that an ex post approach typically maximises overall welfare. However, an ex ante approach can be the preferred option in cases where the entrant has a large cost advantage over the incumbent.
Keywords: K21; L41; 330; competition policy; monopolisation; predation; enforcement; Wettbewerbspolitik; Verdrängungswettbewerb; Wirkungsanalyse; Duopol; Wohlfahrtseffekt; Theorie